The Influence of Religiosity, Income, and Trust on Income Zakat Intention - Annisa Fitri, Shafiah; Sri Wahyuni, Eka; Harpepen, Andi (El-kahfi | Jurnal Ekonomi Islam, 2025)
This study examines the impact of religiosity, income, and trust on individuals’ intention to pay income zakat in Talo District, Seluma Regency, Indonesia. A quantitative method was employed using a structured questionnaire distributed to 100 eligible Muslim respondents. The analysis was conducted through multiple linear regression. Results demonstrate that religiosity, income, and trust significantly affect zakat payment intention, with religiosity emerging as the strongest predictor. The model explains 50.7% of the variance in zakat intention. These findings suggest that enhancing religious commitment, economic capacity, and institutional trust is vital to fostering zakat compliance, especially in semi-rural communities. The study also underscores the need for targeted awareness campaigns and more transparent zakat management to strengthen public confidence in formal zakat institutions. By integrating behavioral and institutional dimensions, this research contributes to a more comprehensive understanding of Islamic philanthropic behavior in emerging economies.